(untitled) (The Research of Medical Science Review, 2025)
Lower extremity amputation (LEA) represents a devastating yet preventable complication of diabetes mellitus, driven by neuropathy, peripheral artery disease, and infection. This cross-sectional study aimed to identify modifiable risk factors for LEA among 50 consecutive patients undergoing amputation due to diabetic complications at Allied Hospital-2 and Faisalabad Diabetic Centre (April-May 2025). Data collected via structured interviews, medical records, and digital forms revealed critical patterns: most participants (59.2%) had >10-year diabetes duration, with systemic evidence of poor glycemic control – 67.3% monitored blood glucose ≤monthly and 83.7% required hyperglycemia-related hospitalizations. Diabetic foot ulcers preceded amputation in 81.6% of cases, all failing to heal within 4 weeks. Significant comorbidity burdens included hypertension (61.2%), neuropathy (49.0%), and peripheral artery disease (38.8%). Crucially, care discontinuities were prevalent with only 36% receiving preventive foot education before ulcer development, 65.3% reporting medication non-adherence, and 42.8% abandoning post-amputation follow-up – despite 87.8% acknowledging preventability through better self-management. These findings demonstrate that LEA risk escalates through prolonged poor glycemic control, unmanaged comorbidities, and fragmented healthcare delivery, particularly inadequate patient education, therapeutic adherence support, and postoperative continuity. Multidisciplinary interventions integrating rigorous metabolic management, comorbidity screening, structured self-care education, and coordinated longitudinal care are essential to reduce preventable amputations in high-risk diabetic populations.